Supporting parents in taking care of their infants admitted to a neonatal intensive care unit: a prospective cohort pilot study - Giuseppe De Bernardo; Maria Svelto; Maurizio Giordano; Desiree Sordino; Marina Riccitelli (BMC, 2017)
Abstract Background Family-Centred Care (FCC) is recognized as an important component of all paediatric care, including neonatal care, although practical clinical guidelines to support this care model are still needed in Italy. The characteristics and services for families in Italian NICUs show a lack of organization and participation. Methods The first aim was to compare satisfaction and stress levels in two groups of parents: an FCC group and a non-FCC group (NFCC). The second aim was to evaluate body weight gain in the newborns enrolled. This non-randomized, prospective cohort pilot study was conducted in a single level III NICU at a hospital in Naples, Italy. A cohort of newborns in the NICU, with their parents were enrolled between March 2014 and April 2015 and they were divided into two groups: the FCC group (enrolled between October 2014 and April 2015) remained in the NICU for 8 h a day with FCC model; the NFCC group (enrolled between March 2014 and September 2014) was granted access to the NICU for only 1 hour per day. At discharge, both parent groups completed the Parental Stressor Scale (PSS)-NICU and a questionnaire to assess their satisfaction. In addition, we compared scores from the mothers and fathers within and between groups and the body weights of the newborns in the two groups at 60 days. Results Parents participating in the FCC group were more satisfied and less stressed than those in the NFCC group. Infants in the FCC group also showed increased body weight after 60 days of hospital stay. Conclusions Despite our small population, we confirm that routine adoption of a procedure designed to apply a FCC model can contribute to improving satisfaction and distress among preterm infants' parents. Future multi-centre, randomized, controlled trials are needed to confirm these findings.